Analisis dan Implementasi Knowledge Management System pada Bagian Administrasi PT HASIL KARYA TAMBANG Menggunakan Metode KMSLC DAN Analisis PIECES - Rokhman, Nur; Edy Siswanto; Nur Chakiki Ramadiansyah (LPPM Politeknik Pratama Kendal, 2023)
The problem that often occurs at PT.Hasil Karya Tambang, especially in the administration section, is the availability of information in each branch office that is not qualified in solving problems that are often raised by customers so that it takes longer to handle them. With the Knowledge Management System, all problems in the field of information availability for administration can be overcome, where later the Knowledge Management System will be Web-oriented, which can be accessed easily, and can quickly provide solutions for customers who make complaints at various branch office of PT Karya Karya Tambang. And with this Knowledge Management System, the company can better analyze what problems are most often experienced and can fix them.